UPAYA MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK DENGAN PEMBELAJARAN KONTEKSTUAL HUMANISTIK - Simon Panjaitan (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2020)
This study aims to determine the increase in students' creative thinking on the Social Arithmetic Material at SMP Yapim Medan. This type of research is classroom action research with 26 research subjects. The instruments used were tests and observations. The average value of teacher observation in cycle I was 75% and increased in cycle II to 84.38% in the good category, while the average value of student activity observation in the first cycle was 62.25% in the good category, where as in cycle II it was 68.63% in the good category. The average of creative thinking of students in the initial test obtained 44.32% increased to 69.92% in the first cycle and 78.04% in the second cycle. Because the activities of students increased, teacher observation increased and the ability of creative thinking of students also increased from cycle I to cycle II, it can be concluded that the students' creative thinking ability with humanistic contextual learningincreases.